The Influence of Company Growth, Profitability, Leverage, Financial Condition, and Previous Years’ Audit Opinions on Going Concern Audit Opinion (Empirical Study of the Real Estate and Property Industry Listed on the Indonesian Stock Exchange for the 2019-2021 Period) - Yuli Tri Cahyono; Benny Tjahjono; Mahameru Rosy Rochmatullah; Kusuma Wijayanto (Riset Akuntansi dan Keuangan Indonesia, 2023)
A going concern audit opinion is an audit opinion given on an entity’s financial statements when its conditions differ from the assumption of business continuity. This research, therefore, aims to ascertain the impact of company growth, profitability, leverage, financial condition, and previous years’ audit opinions on the going concern audit opinions. The data used is quantitative. The real estate and property industry classification companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2021 period were the objects of the research. Purposive sampling was used for the sampling, and 126 companies were obtained. The logistic regression analysis was employed in the data analysis method. According to the study findings, while previous year audit opinions had an impact, company growth, profitability, leverage, and financial condition had no impact on going concern audit opinion.